Examining the effects of work values on employee commitment in UAE via literature survey - Taresh Saif Suhail Al Marri, Maryam; Abdul Majid, Abdul Halim; Abdullah, Haim Hilman (Kiban Research Publications, 2019)
Objective Employee commitment remains long standing determinant of the survival of organizations, although the state of the existing body of knowledge on employee commitment signified that most of the existing studies were primarily conducted in the Western business contexts, and less is known about employee commitment and its correlates in the non-Western countries. In addition, some scholars reiterate that organizations would accomplish goals that individuals cannot do alone, but this could only be made possible via employee commitment and productivity. If this position is anything to go by, then it could be said that employee commitment is paramount to organizational survival. Thus, factors that could enhance the commitment of workforce are worthy-researching. Methods Via literature survey, the current study presented a logic-based and empirically-based conceptual discussion to signify that work values, which connote career-growth, social interaction, security and economic, stability and freedom, and recreation, health and transport, could exert influence on employee commitment. Results and Conclusion Based on the literature review, it could be stressed that the work values’ dimensions, as identified previously, could enhance employee commitment. With this, it could be said that the present body has widened the scope of the existing body of knowledge in the organizational commitment research area. However, future studies can further this study empirically which involves data collection on the same constructs of the study and data analyses. Implications of the study were also discussed.